English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

sqrt 18 simplfies to 2 sqrt 3
so i have 2 sqrt 3 - sqrt 3 / sqrt 6
the two sqrt 3's cancel out so i have 2 / sqrt 6
to simplify it further I multiply 2/sqrt 6 by sqrt 6 /sqrt6
which gives me 2 sqrt 6 / 6
is this the right answer?

2007-03-29 16:29:13 · 8 answers · asked by jinglexjangle 1 in Science & Mathematics Mathematics

Can you show me how to get the right answer?

2007-03-29 16:34:20 · update #1

8 answers

No

sqrt(18) = 3sqrt(2)

3sqrt(2)- sqrt 3 / sqrt 6

multiply by 1 (sqrt(6)/sqrt(6))

3sqrt(12) - sqrt(18)/ 6

6sqrt(3) - 3sqrt(2)/6

3sqrt(3) - sqrt(2)/3

2007-03-29 16:35:00 · answer #1 · answered by yup5 2 · 0 0

The important principles about square roots are:
sqrt(AB) = sqrt(A) sqrt(B) and
sqrt(A / B) = sqrt(A) / sqrt(B)
1 / sqrt(A) = sqrt(A) / A
BUT REMEMBER sqrt(A+B) is not equal to sqrt(A) + sqrt(B)

So, looking at the two parts separately:
sqrt(18) = sqrt(9) sqrt(2) = 3 sqrt(2)

And
sqrt(3) / sqrt(6) = sqrt(3) / sqrt(2) sqrt(3)
= 1 / sqrt(2) = sqrt(2) / 2 = (1/2) sqrt(2)

So putting these together we have
sqrt(18) - sqrt(3) / sqrt(6) = 3 sqrt(2) - (1/2) sqrt(2)
= (5/2) sqrt(2)

2007-03-29 18:02:30 · answer #2 · answered by jim n 4 · 0 0

3 sqrt 2 - sqrt 3 / sqrt 6???

Isn't sqrt 18 at its most simplified point 3 sqrt 2
(not what you put 2 sqrt 3)

2007-03-29 16:40:35 · answer #3 · answered by michiganmatt1414 1 · 0 0

The correct answer is (3)^1/2 - (1/2)^1/2 = 1.025 or for all practical purposes = 1.

(18)^1/2 - (3)^1/2 all divided by (2x3)^1/2 simplifies to:
3 - (3/2)^1/2 all divided by (3)^1/2 = 3/(3)^1/2 - (1/2)^1/2 =:
(3)^1/2 - .7071067 = 1.7320506 - ,7071067 = 1.025 which simplifies to 1.

2007-03-29 18:08:40 · answer #4 · answered by Mad Mac 7 · 0 0

We use algebraic substitution. enable u = ?x this suggests u = x^(a million/2) and subsequently du = (a million/2)x^(-a million/2) dx du = a million / [2x^(a million/2)] dx du = a million / [2 ?x] dx dx = 2 ?x du dx = 2 u du Now substitute into the unique fundamental ? (?x) / (?x - 3) dx = ? [u / (u - 3)] 2u du ? (?x) / (?x - 3) dx = ? 2u² / (u - 3) du Now enable z = u - 3 (meaning z + 3 = u) dz = du ? 2u² / (u - 3) du = ? [2(z + 3)² / z] dz ? 2u² / (u - 3) du = ? [2(z² + 6z + 9) / z] dz ? 2u² / (u - 3) du = ? [(2z² + 12z + 18) / z dz ? 2u² / (u - 3) du =? [2z + 12 + 18/z] dz ? 2u² / (u - 3) du = z² + 12z + 18 ln |z| + ok ? 2u² / (u - 3) du = (u - 3)² + 12(u - 3) + 18 ln |u - 3| + ok ? (?x) / (?x - 3) dx = (?x - 3)² + 12(?x - 3 ) + 18 ln |?x - 3| + ok ? (?x) / (?x - 3) dx = (?x - 3)(?x - 3) + 12(?x - 3 ) + 18 ln |?x - 3| + ok ? (?x) / (?x - 3) dx = x - 6?x + 9 + 12?x - 36 + 18 ln |?x - 3| + ok ? (?x) / (?x - 3) dx = x + 6?x - 27 + 18 ln |?x - 3| + ok Now -27 + ok might properly be recognised as a clean consistent, say c ? (?x) / (?x - 3) dx = x + 6?x + 18 ln |?x - 3| + c Phew ! enable me comprehend in case you elect for to communicate added via clicking on my profile and emailing me.

2016-11-24 22:55:48 · answer #5 · answered by ? 3 · 0 0

u cant subtract different sqrt numbers or add them either

2007-03-29 16:32:42 · answer #6 · answered by BENNETH[[98]] 2 · 0 3

sqrt18 = 3 sqrt2 ???

2007-03-29 16:36:59 · answer #7 · answered by Anonymous · 0 1

sqrt18=3sqrt2
so
3sqrt2-sqrt3/sqrt6=3sqrt2/sqrt6-sqrt3/sqrt6=3sqrt(2/6)-sqrt(3/6)=3sqrt(1/3)-sqrt(1/2)=3sqrt3/3-sqrt2/2=sqrt3-sqrt2/2

2007-03-29 16:38:01 · answer #8 · answered by djin 2 · 0 0

fedest.com, questions and answers